A novel approach to energy harvesting from vehicle suspension system: Half-vehicle model. (1st September 2017) - Wei, Chongfeng; Taghavifar, Hamid
Abstract: Vehicles are subject to a variety of road unevenness and random road excitations that potentially cause the vehicle to undergo a significant amount of energy dissipation. The energy loss due to vibration can be harvested/recaptured from the vehicle suspension system and the present paper aims to assess the energy harvesting potential from vehicle suspension under harmonic and random road excitations. In this manner, a mathematical model of half vehicle model was developed and different parameters such as magnitude, frequency, vehicle velocity and the relative velocity between the sprung mass and front and rear unsprung masses were included for harmonic based road type. For random excitations, two typical roads of highway with gravels and smooth runway were used and the results of average power were analysed. It was concluded that for the average harvested power versus vehicle velocity, the greatest value of 57.84 W is obtained at 13 km/h. Also, the average power increases by road amplitude with the minimum and maximum values of 51.54 and 1289 W. For the random excitations, the amount of instantaneous power that corresponds to highway with gravels is much greater than that of smooth highway and by the increase of vehicle velocity from 10 to 50 km/h, there is an increase of average power for the both of tested randomly distributed irregular road types. Highlights: Energy harvesting of half vehicle model for harmonic and random road excitations. The effect of road frequency, velocity and road amplitude on energy harvesting. Studying the energy harvesting of vehicle bounce and pitch motions (4DOF system). For the random excitation, smooth highway and highway with gravels were studied. Pitch motion of vehicle has a considerable effect on the potential harvested power.